The Aging Imperative in Maine: Present Realities and Future Prospects - Miltiades, Helen.; Kaye, Lenard (Maine Policy Review, 2003)
Maine has one of the oldest populations in the United States. In this article, Helen Miltiades and Lenard Kaye, guest editor for this special issue, provide an overview of Maine’s aging population and the challenges—and opportunities—faced in the “revolution in aging” that is taking place. They point out how the growing older adult population is expected to place greater demands on family caregivers, on the health and long-term care systems, and on state and federal budgetary and policy decisions. Describing some of Maine’s innovative public and private sector responses, they note that Maine has been in the forefront in providing home and community-based care for its frailer elders. At the same time, they emphasize that the aging population presents expanded opportunities, as increasing numbers of healthier older adults choose to remain in the labor force, to participate in education, and to play active roles in philanthropy, the arts, and as volunteers.